2016
DOI: 10.1264/jsme2.me16015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic-Loading-Rate Reduction on Sludge Biomass and Microbial Community in a Deteriorated Pilot-Scale Membrane Bioreactor

Abstract: The effects of a precipitous decrease in the inlet organic loading rate on sludge reductions and the microbial community in a membrane bioreactor were investigated. The sludge biomass was markedly reduced to 47.4% of the initial concentration (approximately 15,000 mg L−1) within 7 d after the organic loading rate was decreased by half (450 to 225 mg chemical oxygen demand L−1 d−1). An analysis of the microbial community structure using high-throughput sequencing revealed an increase in the abundance of faculta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…2). Our other results, that the composition of overall classes was not changed between sampling periods, was also consistent with those by the other conventional techniques (29, 30) (Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…2). Our other results, that the composition of overall classes was not changed between sampling periods, was also consistent with those by the other conventional techniques (29, 30) (Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
“…As a new finding through our method, which has not been reported by the other conventional techniques (23, 26-30, 32), the present results indicated that different homogeneous bacteria were numerically dominant in all three MBRs individually, whose numbers were high enough to affect the performance of the reactor as a single strain. The numerically dominant bacteria in A farm were the homogeneous Arthrobacter genotype and the homogeneous Burkholderi a genotype (AB299593) (Table 1a, 1b), while those in B had the homogeneous Alphaproteobacteria genotype (Table 2a, 2b), and those in C had the homogeneous Betaproteobacteria genotype (Table 3), which occupied a higher ratio among the detected bacteria (Table 6).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations